Maternity waiting homes and traditional midwives in rural Liberia. Issue 2 (14th August 2013) - Lori, Jody R.; Munro, Michelle L.; Rominski, Sarah; Williams, Garfee; Dahn, Bernice T.; Boyd, Carol J.; Moore, Jennifer E.; Gwenegale, Walter
Abstract: Objective: Maternity waiting homes (MWHs) can reduce maternal morbidity and mortality by increasing access to skilled birth attendants (SBAs). The present analysis was conducted to determine whether MWHs increase the use of SBAs at rural primary health clinics in Liberia; to determine whether traditional midwives (TMs) are able to work with SBAs as a team and to describe the perceptions of TMs as they engage with SBAs; and to determine whether MWHs decrease maternal and child morbidity and mortality. Methods: The present analysis was conducted halfway through a large cohort study in which 5 Liberian communities received the intervention (establishment of an MWH) and 5 Liberian communities did not (control group). Focus groups were conducted to examine the views of TMs on their integration into health teams. Results: Communities with MWHs experienced a significant increase in team births from baseline to post‐intervention (10.8% versus 95.2%, P < 0.001), with greater TM engagement. Lower rates of maternal and perinatal death were reported from communities with MWHs. Conclusion: The reduction in morbidity and mortality indicates that the establishment of MWHs is an effective strategy to increase the use of SBAs, improve the collaboration between SBAs and TMs, and improve maternal and neonatal health.